Oxygen transport and utilisation during exercise in cystic fibrosis: contributors to exercise intolerance. Issue 12 (11th November 2020) - Saynor, Zoe L.; Gruet, Mathieu; Rodriguez‐Miguelez, Paula; Harris, Ryan A.
Abstract : New Findings: What is the topic of this review? This review highlights the central and peripheral mechanisms that alter oxygen transport and utilisation and thereby contribute to exercise limitation in people with cystic fibrosis, considering also viable therapeutic targets for intervention. What advances does it highlight? Although traditionally considered a respiratory condition, pathological intramuscular and cardiovascular changes in people with cystic fibrosis appear to be key determinants of exercise intolerance up until the later stages of respiratory disease. Even young, habitually active patients with normal lung function experience multisystemic abnormalities, which play a role in exercise intolerance. Abstract: Cystic fibrosis (CF) is a complex condition, commonly associated with exercise limitation. The mechanisms responsible for this in CF are of interest, given that lower aerobic fitness is associated with an increased risk of being hospitalised with pulmonary exacerbation, a poorer quality of life and a poorer prognosis. Pathophysiological changes in lung function are considered central to CF, and may contribute to exercise limitation. However, it is now clear that the pathogenesis of exercise limitation in this population is multifactorial, with alterations in cardiovascular, muscle and pulmonary function contributing. Whilst some of these changes are attributable to respiratory disease per se, the CF transmembrane conductance regulator protein is also found in skeletal muscle and the vascular endothelium and can directly alter central and localised oxygen delivery, as well as the ability to effectively extract and utilise oxygen at the myocyte level. Since intense exercise poses considerable challenges to arterial oxygen content and/or blood flow and its supply to the working skeletal muscle, evaluating the exercise physiology of people with CF has helped us understand the mechanisms underlying exercise intolerance. Through several investigations over recent years, we have collectively demonstrated that people with CF exhibit reduced skeletal muscle oxygen extraction and utilisation during exercise, with a lesser contribution from haemodynamic or chronotropic mechanisms. Taken together, our findings highlight the importance of targeting mechanisms of skeletal muscle oxygen utilisation in CF to improve exercise tolerance and we offer potential therapeutic interventional strategies. Abstract :